INFLUENCE OF DESIGN OF VERTICAL CYLINDRICAL CHARGES ON CRUSHING OF ORE - Eremenko A.A.; Fefelov S.V.; Mashukov I.V. (My University, 2001)
Process of crushing the ore with the use of explosion has been considered. Laboratory and natural investigations of the process have been performed. Influence of vertical cylindrical explosive charge on degree of crushing the rock mass has been studied. Results of the investigations have shown that the explosive charge with increased diameter is efficient. Necessity to create raise with cross section of up to 1 m2 has been found. Parameters of the blasting and drilling operations have been determined. It has been shown that the vertical concentrated charges with inert gaps provide decrease in consumption of explosive for secondary crushing.